2002
DOI: 10.1021/jf011291d
|View full text |Cite
|
Sign up to set email alerts
|

Proteolysis in Hispánico Cheese Manufactured Using a Mesophilic Starter, a Thermophilic Starter, and Bacteriocin-Producing Lactococcus lactis Subsp. lactis INIA 415 Adjunct Culture

Abstract: Lactococcus lactis subsp. lactis INIA 415, a strain harboring the structural genes of bacteriocins nisin Z and lacticin 481, was used as adjunct culture in the manufacture of Hispánico cheese with a mesophilic starter and a thermophilic starter of high aminopeptidase activity. Addition of the bacteriocin producer promoted early lysis of mesophilic and thermophilic starter bacteria. Extracellular aminopeptidase activity in 7-day-old cheese made using mesophilic and thermophilic starters plus bacteriocin produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
44
3
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 30 publications
18
44
3
3
Order By: Relevance
“…lactis INIA 415, reaching on day 1 counts in control cheese 0.83 log units higher than in experimental cheese. After 75 days, counts of thermophilic LAB in control cheese were still 0.47 log units higher than in experimental cheese, in agreement with the work by Garde et al (2002), who found lower counts of thermophilic LAB in cheese made with a bacteriocin-producing adjunct culture than in control cheese.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…lactis INIA 415, reaching on day 1 counts in control cheese 0.83 log units higher than in experimental cheese. After 75 days, counts of thermophilic LAB in control cheese were still 0.47 log units higher than in experimental cheese, in agreement with the work by Garde et al (2002), who found lower counts of thermophilic LAB in cheese made with a bacteriocin-producing adjunct culture than in control cheese.…”
Section: Discussionsupporting
confidence: 90%
“…However, hydrolysis of b-casein took place mostly during the first 24 h, in agreement with previous works (Picon et al, 1994;Garde et al, 2002). On day 1, residual b-casein was significantly lower in control cheese than in experimental cheese, but afterwards values in both cheeses were similar.…”
Section: Article In Presssupporting
confidence: 92%
See 1 more Smart Citation
“…II). This is in agreement with the results reported by others [4,9,13,44]. However, the three cultures showed the same rate of proteolysis (P > 0.05), in ripened Teleme cheeses made with goat's milk.…”
Section: Effect Of Type Of Culturesupporting
confidence: 93%
“…Type A(II) lantibiotics, such as lacticin 481 and related lantibiotics, have demonstrated potential for use in food production. Previous results showed that lacticin 481, because it is active against LAB, can be used to speed cheese ripening by lysing starter cultures and increasing the amounts of intracellular enzymes (12)(13)(14). In addition, lacticin 481 could be used to inhibit the growth of nonstarter bacteria in cheese, which can cause major economic losses (15).…”
mentioning
confidence: 99%